Application of film cooling to an unshrouded HP turbine casing - Collins, M; Chana, K; Povey, T (American Society of Mechanical Engineers, 2016)
In this paper we describe the design, modelling and experimental testing of a film cooling scheme employed on an unshrouded HP rotor casing.